2022
DOI: 10.33192/smj.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Presentation in Pheochromocytoma: What We Should be Aware

Abstract: Pheochromocytoma is a catecholamine-producing tumor that although being a rare disease, it poses diagnostic problems because its clinical presentation often mimics certain diseases, including cardiovascular disorders. The effects of excessive catecholamine secretion cause a variety of cardiovascular presentations ranging from hypertension to life-threatening cases such as hypertensive emergency, shock, supraventricular or ventricular arrhythmias, pulmonary edema, and acute coronary syndromes. The principal med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kalantar et al (2013) found that elevated platelet count and activation, as well as arrhythmias, appeared to be the most likely contributors to the occurrence of sudden cardiovascular events, including death, in cachexia patients. Patients with cachexia might develop atherosclerotic plaques, which can increase the risk of developing acute coronary syndrome and/ or death due to sudden cardiac diseases, as a result of increased platelet count and activation accompanied by endothelial dysfunction and increased pro-inflammatory cytokines (Molnar et al 2011, Fatkhullina et al 2016, Anaszewicz & Budzyński 2017, Amalia et al 2022. They could be more prone to developing arrhythmias, particularly atrial fibrillation (Arámbula-Garza et al 2016, Anaszewicz & Budzyński 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Kalantar et al (2013) found that elevated platelet count and activation, as well as arrhythmias, appeared to be the most likely contributors to the occurrence of sudden cardiovascular events, including death, in cachexia patients. Patients with cachexia might develop atherosclerotic plaques, which can increase the risk of developing acute coronary syndrome and/ or death due to sudden cardiac diseases, as a result of increased platelet count and activation accompanied by endothelial dysfunction and increased pro-inflammatory cytokines (Molnar et al 2011, Fatkhullina et al 2016, Anaszewicz & Budzyński 2017, Amalia et al 2022. They could be more prone to developing arrhythmias, particularly atrial fibrillation (Arámbula-Garza et al 2016, Anaszewicz & Budzyński 2017.…”
Section: Discussionmentioning
confidence: 99%